Response of diverse groups of sorghum [Sorghum bicolor (L.) Moench] genotypes to low temperature stress at anthesis - Reddy, P. Sanjana; Patil, J.V.; Krishna, T. Phani (The Indian Journal of Genetics and Plant Breeding, 2016)
Rapid productivity increases has not been realized in winter/post-rainy/rabi sorghum, an important food crop in the semi-arid tropical regions of India.The crop is dominated with varieties as poor seed set due to susceptibility to cold stress is noticed in the hybrids. Hence, before initiation of breeding program to bring in tolerance to cold stress, diverse group of breeding material that included 8 varieties, 7 maintainer lines, 5 restorer lines and a hybrid were screened for tolerance to cold stress in two dates of sowing for pollen viability and germinability apart from other agronomic traits. Date of sowing significantly influenced pollen germinability and the influence of the cooler night temperatures was more than the genetic background. In contrast, pollen viability had less phenotypic plasticity and highly heritable.The loss of grain yield (open panicle grain yield-selfed panicle grain yield) was about 5g/panicle in varieties while it was 1.9g/panicle in restorer lines and about 5.7g/panicle in B-lines.The loss in grain yield was highest in the hybrid at about 22.9g. Higher grain yields can be attained in the hybrid with improvement in the pollen viability and germinability. The germinability percentage was positively associated with selfed panicle weight, grain yield and harvest index while the viability percentage did not show such association.The germinability percentage was more linearly related in R lines followed by B lines and varieties.